Carbon black rubber composite material and preparation method thereof

By combining multifunctional natural rubber with modified carbon black composition and modified concave and concave rods, a carbon black rubber composite material with a multivariate crosslinking network was prepared, which solved the problem of insufficient wear resistance and bending fatigue resistance in the prior art, and achieved high wear resistance and low rolling resistance of the tire material.

CN120535844AActive Publication Date: 2025-08-26GUANGXI CHANGKE NEW MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510872655.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-27
Publication Date
2025-08-26
Estimated Expiration
2045-06-27

AI Technical Summary

Technical Problem

The wear resistance and bending fatigue resistance of existing carbon black rubber composite materials are poor, making it difficult to meet the tire needs of low rolling resistance and low carbon emissions.

Method used

The carbon black rubber composite material is prepared by kneading and high-temperature vulcanization to form a multi-functional crosslinking network to improve the motion resistance and dispersion of the molecular chain and enhance the compatibility between materials.

Benefits of technology

It significantly improves the wear resistance and bending fatigue resistance of carbon black rubber composite materials, enhances the mechanical properties and processing fluidity of the material, reduces stress concentration caused by carbon black agglomeration, and improves the use performance of the tire.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of composite materials, in particular to a carbon black rubber composite material and a preparation method thereof. 58-68 parts of a reinforcing material; 2.8 to 4.3 parts of an anti-aging agent; 1.1 to 1.8 parts of an accelerant; 1.3 to 2.5 parts of a vulcanizing agent; 2-4.6 parts of an auxiliary vulcanizing agent; 5-9.3 parts of a plasticizer; the carbon black rubber composite material is obtained by mixing the rubber, the reinforcing material, the vulcanizing agent and other assistants and then placing the mixture in a mold for high-temperature vulcanization. Wherein part of the natural rubber is subjected to multi-functional modification, so that the formation of a multi-element cross-linked network among the rubber, the reinforcing material and other auxiliaries in the composite material is facilitated; the reinforcing material is prepared from high-wear-resistance carbon black, a modified carbon black composition, zinc methacrylate and modified attapulgite, the synergistic effect is achieved, the wear resistance and flex fatigue resistance of the rubber material are effectively enhanced, and the rubber material has wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a carbon black rubber composite material and a preparation method thereof. Background Art

[0002] In recent years, countries around the world have increasingly focused on environmental issues in tire manufacturing and use. Regulatory authorities at all levels in my country and consumers have also imposed stricter performance requirements on tire products. Therefore, minimizing rolling resistance while maintaining excellent wear resistance and high grip on both dry and wet roads, resulting in "green tires" with low fuel consumption and low carbon emissions, has become the mainstream development direction of the global tire industry.

[0003] Among tire rubber materials, carbon black is the most widely used and largest-volume reinforcing filler. Its low price and high reinforcement properties give it an irreplaceable strategic position in the tire industry. However, when carbon black is added to rubber, due to its high structure and high specific surface area, it is very prone to aggregation. While this aggregation, forming a filler network, provides reinforcement, the relative slip and friction between carbon black and carbon black, and between carbon black and rubber molecular chains, under dynamic loading conditions, leads to significant hysteresis losses, hindering energy conservation and emission reduction. Furthermore, the small diameter and large specific surface area of ​​primary carbon black particles result in extremely high surface energy, making them prone to agglomeration. They typically exist in rubber as large aggregates, making nanoscale dispersion difficult. Under dynamic deformation, internal friction between carbon black particles is severe, leading to high hysteresis heat generation. Furthermore, carbon black and rubber are primarily bonded through physical adsorption. During dynamic deformation, rubber molecular chains are prone to slip and adsorption-desorption processes, which also contribute to certain hysteresis losses. To address this issue, technicians are continuously adjusting and improving rubber composite materials.

[0004] In the prior art, for example, patent document CN114672079B discloses a tread rubber composition, mixing process, and tire with high wet grip and low hysteresis loss. The composite rubber material utilizes modified silica in combination with other fillers to impart low rolling resistance, good wet skid resistance, and good wear resistance. However, compared with carbon black, the composite rubber material suffers from shortcomings in tire performance, such as poor vulcanization and processing properties, and low strength, damage resistance, and wear resistance. Patent document CN113801376 discloses a method for modifying carbon black obtained from waste tire pyrolysis, a rubber composite material, and its application. The modified carbon black obtained from tire pyrolysis is modified using plasma technology, which improves the reinforcement of the rubber matrix. However, the wear resistance and flex fatigue resistance of the rubber composite material need to be further improved.

[0005] Therefore, according to the above-mentioned related technologies, there is an urgent need to develop a carbon black rubber composite material and a preparation method thereof. Summary of the Invention

[0006] In view of this, the object of the present invention is to provide a carbon black rubber composite material and a preparation method thereof, so as to solve the problem of poor wear resistance and flex fatigue resistance of the rubber composite material in the prior art.

[0007] Based on the above objectives, the present invention provides a carbon black rubber composite material and a preparation method thereof.

[0008] A carbon black rubber composite material comprising the following raw materials in parts by weight: Rubber 55-72 parts; reinforcing material 58-68 parts; antioxidant 2.8-4.3 parts; accelerator 1.1-1.8 parts; vulcanizing agent 1.3-2.5 parts; co-vulcanizing agent 2-4.6 parts; plasticizer 5-9.3 parts; The rubber is obtained by mixing natural rubber and multifunctional natural rubber in a mass ratio of 17-22:8.3-11.5; The multifunctional natural rubber is prepared from natural rubber and maleic anhydride; The reinforcing material is obtained by mixing high wear-resistant carbon black, modified carbon black composition, zinc methacrylate and modified attapulgite in a mass ratio of 5-8:12-17.5:3.5-5.5:4.9-7.2; The modified carbon black composition is prepared from carbon black, activated biochar and polyvinyl alcohol; The modified attapulgite is prepared from attapulgite, maleic anhydride and 3-methacryloxypropyltrimethoxysilane.

[0009] Preferably, the preparation method of the multifunctional natural rubber is as follows: The natural rubber and 70% by mass of sodium hydride were placed in a Haake torque rheometer at a speed of 35-45 r / min, heated to 98-103°C, reacted for 15-20 minutes, and then maleic anhydride was added and the reaction was continued for 15-20 minutes to obtain a multifunctional natural rubber. The mass ratio of the natural rubber, sodium hydride with a mass fraction of 70%, and maleic anhydride is 100-120:0.8-2.1:7.2-9.5.

[0010] Preferably, the preparation method of the modified attapulgite is as follows: Step A1. The attapulgite was baked at high temperature, then ground in distilled water, and acidified with 4.0 mol / L HCl to obtain activated attapulgite; Step A2. The activated attapulgite, 3-methacryloxypropyltrimethoxysilane, and anhydrous ethanol were added to a flask, stirred for 3-5 minutes, and then dispersed by ultrasonic vibration for 1.5-2 hours. The mixture was heated for reaction. After the reaction was completed, the mixture was centrifuged and washed with ethanol three times to obtain a silanized attapulgite. Step A3. Under a nitrogen atmosphere, the silanized attapulgite and toluene were added to a three-necked flask, ultrasonically dispersed for 30-40 minutes, and then dibenzoyl peroxide was added. The temperature was raised to 82-90°C and stirred for 20-30 minutes. The maleic anhydride-toluene solution was added dropwise to the reaction system, heated to reflux, and after the reaction was completed, cooled to room temperature, centrifuged, washed with ethanol, and dried to obtain a modified attapulgite.

[0011] Preferably, the high temperature baking in step A1 is performed at a temperature of 300-380° C. and a time of 2-2.5 h; The particle size of the ground attapulgite is ≤200 mesh; The ratio of the activated attapulgite, 3-methacryloxypropyltrimethoxysilane and anhydrous ethanol used in step A2 is 5-7.3 g: 100-143 mL: 5.5-8.1 mL; The temperature during the heating reaction is 75-82° C. and the time is 22-24 hours.

[0012] Preferably, the usage ratio of the silanized attapulgite, toluene, dibenzoyl peroxide and maleic anhydride-toluene solution in step A3 is 8-13 g:135-220 mL:0.3-0.8 g:25-42 mL; The heating reflux temperature is 85-95°C and the time is 4.5-6h; The ratio of maleic anhydride to toluene in the maleic anhydride-toluene solution is 3.2-5.5 g:25-42 mL.

[0013] Preferably, the preparation method of the modified carbon black composition is as follows: Step B1. Soak the biochar in a 35%-40% KOH solution, stir for 12-13 hours, let it stand for 20-24 hours, and then dry it at 110-120°C for 48-50 hours. After cooling, wash it twice with 1 mol / L hydrochloric acid solution and deionized water, and then dry it at 60-70°C for 3-4 hours to obtain activated biochar. Step B2. γ-aminopropyltriethoxysilane, ethanol and water were added to a beaker, stirred, and the pH of the solution was adjusted to 8-9 with aqueous ammonia to obtain a mixed solution A; Step B3. The carbon black and toluene were added to the reactor and ultrasonically dispersed for 20-30 min. After drying, the mixture was added to the mixed solution A and heated with stirring under a nitrogen atmosphere. After the reaction was completed, the pretreated carbon black was washed and dried; Step B4. Add polyvinyl alcohol to deionized water, heat to 70-80°C, stir evenly, cool to 55-60°C, add pretreated carbon black, ultrasonically disperse for 30-40 minutes, add p-toluenesulfonic acid, continue stirring and introduce nitrogen, heat the reaction at 60-67°C for 2.5-3 hours, and after the reaction is complete, centrifuge, wash, and dry to obtain modified carbon black; Step B5. Add the modified carbon black to deionized water, ultrasonically disperse for 15-20 minutes, add the activated biochar, stir evenly, add glutaraldehyde, adjust the pH of the system to 8-9 with sodium hydroxide, react at 42-50°C for 40-55 minutes, wash, and vacuum dry to obtain a modified carbon black composition.

[0014] Preferably, the mass ratio of the biochar to the 35%-40% KOH solution in step B1 is 1:4.5-5.5; The volume ratio of γ-aminopropyltriethoxysilane, ethanol and water in step B2 is 4-7:55-75:5-8; The amount ratio of carbon black, toluene and mixed solution A in step B3 is 5.5-9 g:22-27 mL:110-135 mL; The temperature during the heating and stirring is 78-83° C. and the time is 4.5-5.5 hours.

[0015] Preferably, the ratio of polyvinyl alcohol, deionized water, pretreated carbon black and p-toluenesulfonic acid in step B4 is 3.5-4.8 g: 85-100 mL: 0.18-0.27 g: 0.03-0.05 g; The usage ratio of the modified carbon black, deionized water, activated biochar and glutaraldehyde in step B5 is 3.5-5.8 g:125-155 mL:8-12.4 g:0.05-0.08 g.

[0016] Preferably, the plasticizer is obtained by mixing paraffin oil 2058 and dibutyl sebacate in a mass ratio of 2-3.5:1; The antioxidant is obtained by mixing antioxidant RD, antioxidant MB and antioxidant 6PPD in a mass ratio of 4-7:2-4:2-4; The vulcanizing agent is obtained by mixing dicumyl peroxide and sulfur in a mass ratio of 3-6:2.1-3.5; The co-vulcanizing agent is obtained by mixing zinc oxide and stearic acid in a mass ratio of 6-9:1-2; The accelerator is 2-thiolbenzothiazole.

[0017] A method for preparing a carbon black rubber composite material comprises the following steps: Step S1. Add rubber to a roller mixer, control the roller temperature to 48-65°C and then plasticize the rubber until the rubber completely wraps around the roller, then cut it with a knife and add an antioxidant and a vulcanizing agent, continue mixing for 3-5 minutes, then add a plasticizer and a reinforcing material in three portions, mix for another 5-8 minutes, add an accelerator and a vulcanizing agent, and cut it again after the rubber has completely absorbed the powder to obtain a rubber mix; Step S2. The rubber mixture is placed in a square mold with a depth of 2.0 mm and subjected to high-pressure vulcanization to obtain a carbon black rubber composite material; The pressure during the high-pressure vulcanization in step S2 is 15-20 MPa, the vulcanization temperature is 140-150° C., and the temperature is 2-2.5 hours.

[0018] Beneficial effects of the present invention: The present invention provides a carbon black rubber composite material and a preparation method thereof. The present invention comprises mixing rubber with a reinforcing material, a vulcanizing agent and other additives, and then placing the mixture in a mold for high-temperature vulcanization, thereby obtaining a carbon black rubber composite material having excellent wear resistance and flex fatigue resistance. The rubber comprises natural rubber and multifunctionalized natural rubber, and maleic anhydride is grafted onto the natural rubber to introduce carbonyl groups, carboxyl groups, and unsaturated carbon-carbon double bonds and other groups into the molecule, thereby facilitating the formation of a multi-component cross-linked network between the rubber, the reinforcing material and other additives in the composite material, thereby further improving the mechanical properties of the composite material, such as wear resistance and tensile strength, increasing the resistance to molecular chain motion, and reducing fatigue damage. In the reinforcing material, carbon black is modified by polyvinyl alcohol and biochar, and the resulting modified carbon black composition has good dispersibility, reduces stress concentration caused by carbon black agglomeration, and effectively improves the mechanical properties of the composite material; in the modified attapulgite, the rigid structure of the attapulgite not only plays a reinforcing role and enhances the compatibility between the rubber matrix and other additives in the composite material, but also improves the dispersion of high-wear-resistant carbon black; and zinc methacrylate, as an unsaturated carboxylic acid metal salt, can form rubber-metal ion cross-linking bonds with the rubber matrix, playing a synergistic role in the reinforcing material. Compared with the existing technology, it has broad application prospects. DETAILED DESCRIPTION

[0019] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to specific embodiments.

[0020] The sources and properties of some of the raw materials used in the present invention are as follows: Maleic anhydride was purchased from Tianjin Hainachuan Technology Development Co., Ltd.; sodium hydride was purchased from Tianjin Bodi Chemical Co., Ltd.; natural rubber was purchased from Yunnan Guangken Rubber Group; stearic acid was purchased from Sichuan Haid Rubber Group Co., Ltd.; sulfur was purchased from Sichuan Haid Rubber Group Co., Ltd.; carbon black N220 was purchased from Shanghai Lisheng Industrial Co., Ltd.; zinc methacrylate was purchased from Nanjing Youhao Additive Chemical Co., Ltd.

[0021] Example 1: A method for preparing a carbon black rubber composite material, comprising the following steps: S1. 100 g of natural rubber and 0.8 g of 70% sodium hydride were placed in a Haake torque rheometer at 35 rpm and heated to 98°C. After reacting for 15 minutes, 7.2 g of maleic anhydride was added and the reaction continued for another 15 minutes to obtain a multifunctional natural rubber. S2. The attapulgite was baked at 300 ° C for 2 h, then ground in distilled water, and acidified with 4.0 mol / LHCl to obtain activated attapulgite; S3. 5 g of activated attapulgite, 100 mL of 3-methacryloxypropyltrimethoxysilane, and 5.5 mL of anhydrous ethanol were added to a flask, stirred for 3 min, and then dispersed by ultrasonic vibration for 1.5 h. The mixture was heated at 75 ° C for 22 h. After the reaction, the mixture was centrifuged and washed with ethanol three times to obtain a silanized attapulgite. S4. Under a nitrogen atmosphere, 8 g of silanized attapulgite and 135 mL of toluene were added to a three-necked flask. After ultrasonic dispersion for 30 min, 0.3 g of dibenzoyl peroxide was added, and the temperature was raised to 82°C and stirred for 20 min. 25 mL of maleic anhydride-toluene solution (wherein the ratio of maleic anhydride to toluene in the maleic anhydride-toluene solution was 3.2 g:25 mL) was added dropwise to the reaction system. The mixture was heated under reflux at 85°C for 4.5 h. After the reaction, the mixture was cooled to room temperature, centrifuged, washed with ethanol, and dried to obtain a modified attapulgite. S5. 1 g of biochar was immersed in 4.5 g of a 35% KOH solution, stirred for 12 h, allowed to stand for 20 h, and then dried at 110°C for 48 h. After cooling, the solution was washed twice with 1 mol / L hydrochloric acid solution and then with deionized water, and then dried at 60°C for 3 h to obtain the activated biochar. S6. 4 mL of γ-aminopropyltriethoxysilane, 55 mL of ethanol, and 5 mL of water were added to a beaker, stirred, and the pH of the solution was adjusted to 8 with aqueous ammonia to obtain a mixed solution A; S7. 5.5 g of carbon black and 22 mL of toluene were added to the reactor and ultrasonically dispersed for 20 min. After drying, the mixture was added to 110 mL of mixed solution A and heated with stirring at 78 ° C for 4.5 h under a nitrogen atmosphere. After the reaction, the pretreated carbon black was washed and dried. S7. 3.5 g of polyvinyl alcohol was added to 85 mL of deionized water, heated to 70 ° C, stirred evenly, cooled to 55 ° C, and then 0.18 g of pretreated carbon black was added. After ultrasonic dispersion for 30 min, 0.03 g of p-toluenesulfonic acid was added. Stirring was continued and nitrogen was introduced. The reaction was heated at 60 ° C for 2.5 h. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain modified carbon black; S9. 3.5 g of modified carbon black was added to 125 mL of deionized water and ultrasonically dispersed for 15 min. 8 g of activated biochar was added and stirred uniformly. 0.05 g of glutaraldehyde was added and the pH of the system was adjusted to 8 with sodium hydroxide. The mixture was reacted at 42°C for 40 min, washed, and vacuum dried to obtain a modified carbon black composition. S10 17g of natural rubber, 8.3g of multifunctional natural rubber was mixed to obtain a rubber; 5g of high wear-resistant carbon black, 12g of the modified carbon black composition, 3.5g of zinc methacrylate and 4.9g of modified attapulgite were mixed to obtain a reinforcing material; S11. Rubber was added to a roller mixer, and the roller temperature was raised to 48°C. The rubber was plasticized until the rubber completely wrapped around the roller. Subsequently, the rubber was cut and an antioxidant and a vulcanizing agent were added. Mixing was continued for 3 minutes. The plasticizer and reinforcing material were then added in three portions. After mixing for another 5 minutes, an accelerator and a vulcanizing agent were added. After the rubber was completely eaten, the rubber was cut again to obtain a rubber mix. S12. Place the rubber mixture in a square mold with a depth of 2.0 mm and vulcanize it at a pressure of 15 MPa and a vulcanization temperature of 140°C for 2 h to obtain a carbon black rubber composite material.

[0022] Example 2: A method for preparing a carbon black rubber composite material, comprising the following steps: S1. 110 g of natural rubber and 1.4 g of 70% sodium hydride were placed in a Haake torque rheometer at 40 rpm and heated to 100°C. After reacting for 18 minutes, 8.3 g of maleic anhydride was added and the reaction continued for another 18 minutes to obtain a multifunctional natural rubber. S2. The attapulgite was baked at 340 ° C for 2 h, then ground in distilled water, and acidified with 4.0 mol / LHCl to obtain activated attapulgite; S3. 6.2 g of activated attapulgite, 121 mL of 3-methacryloxypropyltrimethoxysilane, and 6.8 mL of anhydrous ethanol were added to a flask, stirred for 4 min, and then dispersed by ultrasonic vibration for 1.5 h. The mixture was heated at 80 ° C for 23 h. After the reaction, the mixture was centrifuged and washed with ethanol three times to obtain a silanized attapulgite. S4. Under a nitrogen atmosphere, 10 g of silanized attapulgite and 175 mL of toluene were added to a three-necked flask. After ultrasonic dispersion for 35 min, 0.55 g of dibenzoyl peroxide was added, and the temperature was raised to 86°C and stirred for 25 min. 34 mL of maleic anhydride-toluene solution was added dropwise to the reaction system (wherein the ratio of maleic anhydride to toluene in the maleic anhydride-toluene solution was 4.3 g:34 mL). The reaction was heated under reflux at 90°C for 5.5 h. After completion of the reaction, the mixture was cooled to room temperature, centrifuged, washed with ethanol, and dried to obtain a modified attapulgite. S5. 1 g of biochar was immersed in 5 g of a 40% KOH solution, stirred for 12.5 h, allowed to stand for 22 h, and then dried at 115°C for 49 h. After cooling, the solution was washed twice with 1 mol / L hydrochloric acid and then with deionized water, and then dried at 65°C for 3.5 h to obtain the activated biochar. S6. 5.5 mL of γ-aminopropyltriethoxysilane, 65 mL of ethanol, and 6.5 mL of water were added to a beaker, stirred, and the pH of the solution was adjusted to 8 with aqueous ammonia to obtain a mixed solution A; S7. 7.3 g of carbon black and 25 mL of toluene were added to the reactor and ultrasonically dispersed for 25 min. After drying, the mixture was added to 125 mL of mixed solution A and heated with stirring at 80 ° C for 5 h in a nitrogen atmosphere. After the reaction, the pretreated carbon black was washed and dried; S7. 4.1 g of polyvinyl alcohol was added to 93 mL of deionized water, heated to 75 ° C, stirred evenly, cooled to 58 ° C, and then 0.22 g of pretreated carbon black was added. After ultrasonic dispersion for 35 min, 0.04 g of p-toluenesulfonic acid was added. Stirring was continued while nitrogen was introduced. The reaction was heated at 64 ° C for 3 h. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain modified carbon black; S9. 4.7 g of modified carbon black was added to 140 mL of deionized water and ultrasonically dispersed for 18 min. 10.2 g of activated biochar was added and stirred uniformly. 0.065 g of glutaraldehyde was added and the pH of the system was adjusted to 9 with sodium hydroxide. The mixture was reacted at 46°C for 50 min, washed, and vacuum dried to obtain a modified carbon black composition. S10 20g of natural rubber, 9.6g of multifunctional natural rubber was mixed to obtain a rubber; 5-8g of high wear-resistant carbon black, 15.3g of the modified carbon black composition, 4.5g of zinc methacrylate and 5.8g of modified attapulgite were mixed to obtain a reinforcing material; S11. Rubber was added to a roller mixer, and the roller temperature was raised to 55°C before the rubber was plasticized until the rubber completely wrapped around the roller. Subsequently, the rubber was cut and an antioxidant and a vulcanizing agent were added. Mixing was continued for 4 minutes, and then the plasticizer and reinforcing material were added in three portions. After mixing for another 7 minutes, an accelerator and a vulcanizing agent were added. After the powder was eaten, the rubber was cut again to obtain a mixed rubber. S12. Place the rubber mixture in a square mold with a depth of 2.0 mm and vulcanize it at a pressure of 18 MPa and a vulcanization temperature of 145°C for 2.5 h to obtain a carbon black rubber composite material.

[0023] Example 3: A method for preparing a carbon black rubber composite material, comprising the following steps: S1. 120 g of natural rubber and 2.1 g of 70% sodium hydride were placed in a Haake torque rheometer at 45 rpm and heated to 103°C. After reacting for 20 min, 9.5 g of maleic anhydride was added and the reaction continued for 20 min to obtain a multifunctional natural rubber. S2. The attapulgite was baked at 380 ° C for 2.5 h, then ground in distilled water, and acidified with 4.0 mol / LHCl to obtain activated attapulgite; S3. 7.3 g of activated attapulgite, 143 mL of 3-methacryloxypropyltrimethoxysilane, and 8.1 mL of anhydrous ethanol were added to a flask, stirred for 5 min, and then dispersed by ultrasonic vibration for 2 h. The mixture was heated at 82 ° C for 24 h. After the reaction, the mixture was centrifuged and washed with ethanol three times to obtain a silanized attapulgite. S4. Under a nitrogen atmosphere, 13 g of silanized attapulgite and 220 mL of toluene were added to a three-necked flask. After ultrasonic dispersion for 40 min, 0.8 g of dibenzoyl peroxide was added, and the temperature was raised to 90°C and stirred for 30 min. 42 mL of maleic anhydride-toluene solution was added dropwise to the reaction system (wherein the ratio of maleic anhydride to toluene in the maleic anhydride-toluene solution was 5.5 g:42 mL). The reaction was heated to reflux at 95°C for 6 h. After the reaction, the mixture was cooled to room temperature, centrifuged, washed with ethanol, and dried to obtain a modified attapulgite. S5. 1 g of biochar was immersed in 5.5 g of a 40% KOH solution, stirred for 13 h, allowed to stand for 24 h, and then dried at 120°C for 50 h. After cooling, the solution was washed twice with 1 mol / L hydrochloric acid and then with deionized water, and then dried at 70°C for 4 h to obtain the activated biochar. S6. 7 mL of γ-aminopropyltriethoxysilane, 75 mL of ethanol, and 8 mL of water were added to a beaker, stirred, and the pH of the solution was adjusted to 9 with aqueous ammonia to obtain a mixed solution A; S7. 9 g of carbon black and 27 mL of toluene were added to the reactor and ultrasonically dispersed for 30 min. After drying, the mixture was added to 135 mL of mixed solution A and heated with stirring at 83 ° C for 5.5 h under a nitrogen atmosphere. After the reaction, the pretreated carbon black was washed and dried. S7. 4.8 g of polyvinyl alcohol was added to 100 mL of deionized water, heated to 80 ° C, stirred evenly, cooled to 60 ° C, and then 0.27 g of pretreated carbon black was added. After ultrasonic dispersion for 40 min, 0.05 g of p-toluenesulfonic acid was added. Stirring was continued and nitrogen was introduced. The reaction was heated at 67 ° C for 3 h. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain modified carbon black; S9. 5.8 g of modified carbon black was added to 155 mL of deionized water and ultrasonically dispersed for 20 min. 12.4 g of activated biochar was added and stirred uniformly. 0.08 g of glutaraldehyde was added and the pH of the system was adjusted to 9 with sodium hydroxide. The mixture was reacted at 50°C for 55 min, washed, and vacuum dried to obtain a modified carbon black composition. S10 22g of natural rubber, 11.5g of multifunctional natural rubber was mixed to obtain a rubber; 8g of high wear-resistant carbon black, 17.5g of the modified carbon black composition, 5.5g of zinc methacrylate and 7.2g of modified attapulgite were mixed to obtain a reinforcing material; S11. Rubber was added to a roller mixer, and the roller temperature was raised to 65°C before the rubber was plasticized until the rubber completely wrapped around the roller. Subsequently, the rubber was cut and an antioxidant and a vulcanizing agent were added. Mixing was continued for 5 minutes, and then the plasticizer and reinforcing material were added in three portions. After mixing for another 8 minutes, an accelerator and a vulcanizing agent were added. After the powder was eaten, the rubber mixture was cut again to obtain a rubber mixture. S12. Place the rubber mixture in a square mold with a depth of 2.0 mm and vulcanize it at a pressure of 20 MPa and a vulcanization temperature of 150°C for 2.5 h to obtain a carbon black rubber composite material.

[0024] Comparative Example 1: Compared with Example 1, this comparative example did not add reinforcing material during the preparation of the carbon black rubber composite material. The remaining steps and parameters were the same and will not be repeated in this comparative example. Finally, a carbon black rubber composite material was obtained.

[0025] Comparative Example 2: Compared with Example 1, this comparative example did not add multifunctional natural rubber during the preparation of the carbon black rubber composite material. The remaining steps and parameters were the same and will not be repeated in this comparative example. Finally, a carbon black rubber composite material was obtained.

[0026] Comparative Example 3: Compared with Example 1, this comparative example only replaces the "reinforcement material" with "high wear-resistant carbon black", and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, a carbon black rubber composite material is obtained.

[0027] Comparative Example 4: Compared with Example 1, this comparative example only replaces the "reinforcement material" with the "modified carbon black composition", and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, a carbon black rubber composite material is obtained.

[0028] Comparative Example 5: Compared with Example 1, this comparative example only replaces the "reinforcement material" with "zinc methacrylate", and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, a carbon black rubber composite material is obtained.

[0029] Comparative Example 6: Compared with Example 1, this comparative example only replaces the "reinforcement material" with the "modified attapulgite", and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, a carbon black rubber composite material is obtained.

[0030] Comparative Example 7: Compared with Example 1, this comparative example only replaces the "modified attapulgite" with the "attapulgite", and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, a carbon black rubber composite material is obtained.

[0031] Performance testing: With reference to the GB / T528 test standard, the carbon black rubber composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 7 were tested for tensile strength and elongation at break; Referring to the GB / T1689 test standard, the wear resistance of the carbon black rubber composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 7 was tested to obtain the Akron wear volume; Referring to the GB / T13934 test standard, the flexural fatigue resistance of the carbon black rubber composites prepared in Examples 1 to 3 and Comparative Examples 1 to 7 was tested to observe whether the samples had cracks after 200,000 cycles of Demesian flexion (5Hz). With reference to GB / T531, the Shore A hardness of the carbon black rubber composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 7 was tested using a Shore hardness tester.

[0032] Table 1 project Tensile strength (MPa) Elongation at break (%) Shore A hardness Demesian flexion (5Hz) 200,000 times <![CDATA[Akron abrasion volume (cm 3 / 1.61 km)]]> Example 1 36.8 528 57 No cracks 0.38 Example 2 37.2 505 59 No cracks 0.33 Example 3 33.7 516 58 No cracks 0.42 Comparative Example 1 25.1 611 52 cracks 0.58 Comparative Example 2 29.5 544 55 No cracks 0.47 Comparative Example 3 25.8 597 53 cracks 0.55 Comparative Example 4 28.3 552 54 No cracks 0.52 Comparative Example 5 28.0 563 55 No cracks 0.49 Comparative Example 6 26.5 583 53 cracks 0.52 Comparative Example 7 25.8 600 55 cracks 0.56 Data Analysis: As can be seen from Table 1, the carbon black rubber composite material prepared by the present invention has better wear resistance and flexural fatigue resistance. This may be because the rubber is composed of natural rubber and multifunctional natural rubber. By grafting maleic anhydride on natural rubber, carbonyl, carboxyl and unsaturated carbon-carbon double bonds are introduced into the molecule, which is conducive to the formation of a multi-crosslinked network between the rubber and the reinforcing material and other additives in the composite material, thereby further improving the mechanical properties such as wear resistance and tensile strength of the composite material, increasing the resistance to molecular chain movement, and reducing fatigue damage; in the reinforcing material, the carbon black is first silanized and then modified by polyvinyl alcohol and biochar. The modified carbon black composition has good dispersibility, weakens the interaction force between carbon black particles, reduces the stress concentration caused by carbon black agglomeration, and the contained porous structure of biochar has a good effect on the modified carbon black. It has a certain adsorption capacity like other small molecule additives, which improves the processing fluidity of rubber. The active groups on the surface of its molecules can also synergize with other additives in the composite material to promote the vulcanization of rubber and effectively improve the mechanical properties of the composite material. In the modified convex rods, the rigid structure of the convex rods plays a reinforcing role and enhances the compatibility between the rubber matrix and other additives in the composite material. At the same time, the high wear-resistant carbon black can be well interspersed in the layered structure of the convex rods, thereby improving the dispersion of the high wear-resistant carbon black. The unsaturated carboxylic acid metal salt zinc methacrylate can undergo homopolymerization and grafting reactions under the action of free radicals generated when diisopropyl peroxide is thermally decomposed, forming polyzinc methacrylate nanoparticles in the vulcanized rubber. While self-polymerization occurs, it also forms an interpenetrating network with multifunctional natural rubber, and the wear resistance and flexural fatigue resistance of the composite material are further improved.

[0033] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Within the scope of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0034] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A carbon black rubber composite material, characterized in that: Including the following raw materials by weight: Rubber 55-72 parts; reinforcing material 58-68 parts; antioxidant 2.8-4.3 parts; accelerator 1.1-1.8 parts; vulcanizing agent 1.3-2.5 parts; co-vulcanizing agent 2-4.6 parts; plasticizer 5-9.3 parts; The rubber is obtained by mixing natural rubber and multifunctional natural rubber in a mass ratio of 17-22:8.3-11.5; The multifunctional natural rubber is prepared from natural rubber and maleic anhydride; The reinforcing material is obtained by mixing high wear-resistant carbon black, modified carbon black composition, zinc methacrylate and modified attapulgite in a mass ratio of 5-8:12-17.5:3.5-5.5:4.9-7.2; The modified carbon black composition is prepared from carbon black, activated biochar and polyvinyl alcohol; The modified attapulgite is prepared from attapulgite, maleic anhydride and 3-methacryloxypropyltrimethoxysilane.

2. The carbon black rubber composite material according to claim 1, characterized in that The preparation method of the multifunctional natural rubber is as follows: The natural rubber and 70% by mass of sodium hydride were placed in a Haake torque rheometer at a speed of 35-45 r / min, heated to 98-103°C, reacted for 15-20 minutes, and then maleic anhydride was added and the reaction was continued for 15-20 minutes to obtain a multifunctional natural rubber. The mass ratio of the natural rubber, sodium hydride with a mass fraction of 70%, and maleic anhydride is 100-120:0.8-2.1:7.2-9.

5.

3. The carbon black rubber composite material according to claim 1, characterized in that The preparation method of the modified attapulgite is as follows: Step A1. The attapulgite was baked at high temperature, then ground in distilled water, and acidified with 4.0 mol / L HCl to obtain activated attapulgite; Step A2. The activated attapulgite, 3-methacryloxypropyltrimethoxysilane, and anhydrous ethanol were added to a flask, stirred for 3-5 minutes, and then dispersed by ultrasonic vibration for 1.5-2 hours. The mixture was heated for reaction. After the reaction was completed, the mixture was centrifuged and washed with ethanol three times to obtain a silanized attapulgite. Step A3. Under a nitrogen atmosphere, the silanized attapulgite and toluene were added to a three-necked flask, ultrasonically dispersed for 30-40 minutes, and then dibenzoyl peroxide was added. The temperature was raised to 82-90°C and stirred for 20-30 minutes. The maleic anhydride-toluene solution was added dropwise to the reaction system, heated to reflux, and after the reaction was completed, cooled to room temperature, centrifuged, washed with ethanol, and dried to obtain a modified attapulgite.

4. The carbon black rubber composite material according to claim 3, characterized in that The high temperature baking in step A1 is performed at a temperature of 300-380° C. and a time of 2-2.5 hours; The particle size of the ground attapulgite is ≤200 mesh; The ratio of the activated attapulgite, 3-methacryloxypropyltrimethoxysilane and anhydrous ethanol used in step A2 is 5-7.3 g: 100-143 mL: 5.5-8.1 mL; The temperature during the heating reaction is 75-82° C. and the time is 22-24 hours.

5. The carbon black rubber composite material according to claim 3, characterized in that The usage ratio of the silanized attapulgite, toluene, dibenzoyl peroxide, and maleic anhydride-toluene solution in step A3 is 8-13 g:135-220 mL:0.3-0.8 g:25-42 mL; The heating reflux temperature is 85-95°C and the time is 4.5-6h; The ratio of maleic anhydride to toluene in the maleic anhydride-toluene solution is 3.2-5.5 g:25-42 mL.

6. The carbon black rubber composite material according to claim 1, characterized in that The preparation method of the modified carbon black composition is as follows: Step B1. Soak the biochar in a 35%-40% KOH solution, stir for 12-13 hours, let it stand for 20-24 hours, and then dry it at 110-120°C for 48-50 hours. After cooling, wash it twice with 1 mol / L hydrochloric acid solution and deionized water, and then dry it at 60-70°C for 3-4 hours to obtain activated biochar. Step B2. γ-aminopropyltriethoxysilane, ethanol and water were added to a beaker, stirred, and the pH of the solution was adjusted to 8-9 with aqueous ammonia to obtain a mixed solution A; Step B3. The carbon black and toluene were added to the reactor and ultrasonically dispersed for 20-30 min. After drying, the mixture was added to the mixed solution A and heated with stirring under a nitrogen atmosphere. After the reaction was completed, the pretreated carbon black was washed and dried; Step B4. Add polyvinyl alcohol to deionized water, heat to 70-80°C, stir evenly, cool to 55-60°C, add pretreated carbon black, ultrasonically disperse for 30-40 minutes, add p-toluenesulfonic acid, continue stirring and introduce nitrogen, heat the reaction at 60-67°C for 2.5-3 hours, and after the reaction is complete, centrifuge, wash, and dry to obtain modified carbon black; Step B5. Add the modified carbon black to deionized water, ultrasonically disperse for 15-20 minutes, add the activated biochar, stir evenly, add glutaraldehyde, adjust the pH of the system to 8-9 with sodium hydroxide, react at 42-50°C for 40-55 minutes, wash, and vacuum dry to obtain a modified carbon black composition.

7. The carbon black rubber composite material according to claim 6, characterized in that The mass ratio of the biochar in step B1 to the 35%-40% KOH solution is 1:4.5-5.5; The volume ratio of γ-aminopropyltriethoxysilane, ethanol and water in step B2 is 4-7:55-75:5-8; The amount ratio of carbon black, toluene and mixed solution A in step B3 is 5.5-9 g:22-27 mL:110-135 mL; The temperature during the heating and stirring is 78-83° C. and the time is 4.5-5.5 hours.

8. The carbon black rubber composite material according to claim 6, characterized in that In step B4, the ratio of polyvinyl alcohol, deionized water, pretreated carbon black, and p-toluenesulfonic acid is 3.5-4.8 g: 85-100 mL: 0.18-0.27 g: 0.03-0.05 g; The usage ratio of the modified carbon black, deionized water, activated biochar and glutaraldehyde in step B5 is 3.5-5.8 g:125-155 mL:8-12.4 g:0.05-0.08 g.

9. The carbon black rubber composite material according to claim 1, characterized in that The plasticizer is obtained by mixing paraffin oil 2058 and dibutyl sebacate in a mass ratio of 2-3.5:1; The antioxidant is obtained by mixing antioxidant RD, antioxidant MB and antioxidant 6PPD in a mass ratio of 4-7:2-4:2-4; The vulcanizing agent is obtained by mixing dicumyl peroxide and sulfur in a mass ratio of 3-6:2.1-3.5; The co-vulcanizing agent is obtained by mixing zinc oxide and stearic acid in a mass ratio of 6-9:1-2; The accelerator is 2-thiolbenzothiazole.

10. The method for preparing the carbon black rubber composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step S1. Add rubber to a roller mixer, control the roller temperature to 48-65°C and then plasticize the rubber until the rubber completely wraps around the roller, then cut it with a knife and add an antioxidant and a vulcanizing agent, continue mixing for 3-5 minutes, then add a plasticizer and a reinforcing material in three portions, mix for another 5-8 minutes, add an accelerator and a vulcanizing agent, and cut it again with a knife after the rubber has completely absorbed to obtain a rubber mix; Step S2. The rubber mixture is placed in a square mold with a depth of 2.0 mm and subjected to high-pressure vulcanization to obtain a carbon black rubber composite material; The pressure during the high-pressure vulcanization in step S2 is 15-20 MPa, the vulcanization temperature is 140-150° C., and the temperature is 2-2.5 hours.

Citation Information

Patent Citations

  • Method for preparing natural rubber / nylon short fibre composite material

    CN101480818A

  • Method for eliminating agglomeration of carbon black by modifying carbon black through polyvinyl alcohol

    CN108624090A

  • Preparation method of composite nano absorbent

    CN108704623A

  • Preparation method of wear-resistant aging-resistant rubber compound filled with coupling modified wood fiber

    CN109054119A